A novel cis antisense RNA AsfD promotes Salmonella enterica serovar Typhi motility and biofilm formation. (May 2020) - Chen, Long; Gu, Liping; Geng, Xinfeng; Xu, Guoxin; Huang, Xinxiang; Zhu, Xiaojue
Abstract: Bacterial non-coding RNAs (ncRNAs) can participate in multiple biological processes, including motility, biofilm formation, and virulence. Using high-throughput sequencing and transcriptome analysis of Salmonella enterica serovar Typhi ( S. Typhi), we identified a novel antisense RNA located at the opposite strand of the flhDC operon. In this study, a northern blot and qRT-PCR were used to confirm the expression of this newfound antisense RNA in S . Typhi. Moreover, 5′ RACE and 3′ RT-PCR were performed to reveal the molecular characteristics of the antisense RNA, which was 2079 nt − 2179 nt in length, covered the entire flhDC operon sequence, and termed AsfD. The level of AsfD expression was higher during the stationary phase of S. Typhi and activated by the regulators, OmpR and Fis. When AsfD was overexpressed, the level of flagellar gene flhDC transcription increased; moreover, the level of fliA and fljB expression, as well as the motility and biofilm formation of S . Typhi were also enhanced. The results of this study suggest that AsfD is likely to enhance the motility and biofilm formation of S . Typhi by up-regulating flhDC expression. Highlights: In this work, a novel antisense RNA located at the opposite strand of the flhDC operon was identified and termed AsfD. AsfD can up-regulate the transcriptional levels of flhDC and other flagellar genes. AsfD enhance the motility and biofilm formation of S. Typhi.